Environmental Awareness of Students at SDN Pauh, Tungkal Jaya District and SDN Mendis Jaya, Bayung Lencir District, Musi Banyuasin Regency - Hizazi, Achmad; Mansur, Fitrini; Bintana, Rizqa Raaiqa; Yosep Tri Krisnanto; Nanang Yuliyapranata (International Journal of Economics, Business and Innovation Research, 2025)
This paper describes the school's efforts to increase environmental awareness of students at SDN Pauh, Tungkal Jaya District, and SDN Mendis Jaya, Bayung Lencir District, Musi Banyuasin Regency. The focus of awareness is seen in daily behavior, such as attitudes towards waste in the surrounding area, concern for plants and animals in the area, and an understanding of the importance of maintaining cleanliness and environmental sustainability. To achieve this goal, both schools carry out various programs such as providing trash cans, environmental simulations, awareness campaigns through t-shirts worn by teachers and school staff, distributing environmental awareness posters, and planting trees around the school